The Relationship Between Working Posture and Musculoskeletal Disorders Among Dental Professional Students at the South Sumatra Provincial Dental and Oral Hospital (RSKGM) - Desi Fitriani; Hema Awalia; Reyne Damalisa (Universitas Muhammadiyah Palembang, 2026)
ABSTRACT Long working hours and static working positions among dentists and dental students can increase the risk of musculoskeletal disorders (MSDs). Complaints of MSDs often arise as a result of maintaining static working postures for prolonged periods during dental and oral care. This study aimed to determine the relationship between working posture and complaints of MSDs among dental students at the South Sumatra Provincial Dental Hospital. This study employed an analytical observational design with a cross-sectional approach. The study sample comprised 77 dental students performing treatments in a seated position across all departments at the South Sumatra Provincial Dental Hospital. Work posture assessment was conducted using the Rapid Upper Limb Assessment (RULA), while MSD complaints were measured using the Nordic Body Map questionnaire. Data analysis was performed using the Chi-square test. The results of the Chi-square test showed a p-value < 0.001 (p < 0.05), indicating a significant association between work posture and MSD complaints among dental students at the South Sumatra Provincial Dental Hospital. Students with lower ergonomic work posture risk tended to experience fewer MSD complaints. It can be concluded that work posture has a significant association with MSD complaints among dental students. The adoption of ergonomic work postures is important to reduce the risk and incidence of musculoskeletal complaints.